Comparison of Different selenium Sources on Performance, Serum Attributes and Cellular Immunity in Broiler Chickens - Hossein Zadeh M; Kermanshahi H; Sanjabi MR; Golian A; Azin M; Majidzadeh-Heravi R (Poultry Science Journal, 2018)
The effects of organic and inorganic sources and concentration (0 and 0.3 mg per kg of diet) of Selenium (Se) on growth performance, blood biochemical and immune system were evaluated in broiler chickens. Chickens were fed corn-soy-based diets formulated to 8 dietary treatments containing no added Se (negative control), negative control plus yeast (positive control), and 6 diets had 0.3 mg/kg of diet supplemented with Se from Availa Se, Sel-plex, SeleMax, Se enriched yeast, sodium selenite and sodium selenate. Four hundred Ross 308 male chickens were randomly divided into 8 treatments and 5 replicates of 10 birds each. Feed intake, body weight gain, and feed conversion ratio were measured at starter (0-10 d), grower (11-24 d), and finisher (25-42 d) periods. On d 24 and 42, one bird from each replicate was killed by cervical dislocation and blood samples were collected to determine blood chemicals, glutathione peroxidase (GPx) activity and heterophile to lymphocyte ratio. Results showed that Se supplementation had no effect on feed intake, body weight gain, and feed conversion ratio of the chickens (P < 0.05). However, blood triglycerides, GPx activity and heterophile to lymphocyte ratio were significantly affected by organic and inorganic Se sources (P < 0.05). Results showed that selenium in organic and inorganic forms didn't have any effect on growth performance and blood parameters but they could improve immune system through increase in GPx activity.